Autopercepción de Habilidades Blandas en practicantes de Psicología - Marcos Salazar, Yesluí Carol (2024)
The article focused on exploring the self-perception of soft skills in students of pre-professional internships in Psychology, recognizing the importance of these personal competencies. It was identified that these skills were linked to the development of competencies required for training as psychologists, especially during their pre-professional practices in different locations assigned by the Psychology study program. A reflective thematic analysis was carried out focused on the experiences of the participants, the principles established by the Code of Ethics of the College of Psychologists of Peru were used. A semi-structured interview technique was used, based on questions that considered the behavior of the interviewee. According to the analysis of the data obtained from the 42 interviews, they were grouped into the 8 dimensions proposed by Universia. It was found that there is a demand to strengthen soft skills, according to their self-perception. The aim is to strengthen the eight skills analyzed, such as managing your time effectively in the face of perceived demands. In addition, they require strengthening the ability to deal with stress, practitioners consider that it is mostly difficult for them to regulate their emotions, experiencing tension, frustration, when they cannot understand how to develop clinical, educational and organizational cases. At the same time, they report that sometimes they lose patience with the irresponsibility of their colleagues, but they do show sensitivity to the cases they deal with. Sometimes it makes it difficult for them to focus on the needs of the client/consultant, making it difficult for them to provide a timely response. They request to strengthen their intrapersonal and interpersonal skills, presenting constant concerns about their performance at their headquarters, influencing their emotional stability. In conclusion, the articulation of the curriculum is required to strengthen the behaviors associated with each of the skills addressed.